2019
DOI: 10.1101/509547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal localization of immune transcripts defines hallmarks and diversity in the tuberculosis granuloma

Abstract: Granulomas are the pathological hallmark of Tuberculosis (TB), and the niche in which bacilli can either grow and disseminate or the immunological microenvironment in which host cells interact to prevent bacterial dissemination. Here, after in situ sequencing, thirty-four immune transcripts in lung sections from Mycobacterium tuberculosis-infected mice were aligned to the tissue morphology at cellular resolution, allowing the analysis of local immune interactions in the granuloma.Co-localizing transcript netwo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
(41 reference statements)
2
1
0
Order By: Relevance
“…Considering that ARG1 and MSR1 are markers for M2 macrophages (Ruffell et al, 2009), we investigated the localization of the markers for M1 macrophages, including inducible nitric oxide synthase (iNOS) and CD68 (Figure 3). Both iNOS and CD68 localized to Rim and Cell regions in necrotic granulomas as reported previously (Carow et al, 2019).…”
Section: Polarization Of Fm Within Necrotic Granulomassupporting
confidence: 84%
See 1 more Smart Citation
“…Considering that ARG1 and MSR1 are markers for M2 macrophages (Ruffell et al, 2009), we investigated the localization of the markers for M1 macrophages, including inducible nitric oxide synthase (iNOS) and CD68 (Figure 3). Both iNOS and CD68 localized to Rim and Cell regions in necrotic granulomas as reported previously (Carow et al, 2019).…”
Section: Polarization Of Fm Within Necrotic Granulomassupporting
confidence: 84%
“…Since the M2 macrophage markers MSR1 and ARG1 were identified as signatures for FM, we additionally investigated the localization of the markers for M1 macrophages, iNOS and CD68 within granulomas. IHC and IFM analyses suggested that M1 macrophages localized to Rim and Cell regions, as reported previously (Carow et al, 2019), and that M1 macrophage-derived FM were present in necrotic and non-necrotic granulomas (Figures 3-6). It is possible that M. tuberculosis growth is partially restricted in M1 macrophages and M1 macrophage-derived FM, while its restriction is attenuated in the FM of Rim region in necrotic granulomas because of the function of neighboring M2 macrophages or M2 macrophagederived FM.…”
supporting
confidence: 81%
“…The integration of scRNAseq with spatial transcriptomics enable us to characterise cellular and tissue responses to infections on regional and global scales. This has been successfully applied to characterise local immune responses to Mycobacterium tuberculosis (Carow et al, 2019) and M. leprae (Ma et al, 2021) and in the heart during viral myocarditis (Mantri et al, 2021). However, to our knowledge, similar approaches have not been implemented to study tissue responses to protozoan parasites.…”
Section: Introductionmentioning
confidence: 99%